Synthesis and electrocatalytic activity towards oxygen reduction reaction of gold-nanostars - G, Oyunbileg; G, Batnyagt; B, Enkhsaruul; Takeguchi, T (Mongolian Journal of Chemistry, 2018)
The oxygen reduction reaction (ORR) is a characteristic reaction which determines the performance of fuel cells which convert a chemical energy into an electrical energy. Aims of this study are to synthesize Au-based nanostars (AuNSs) and determine their preliminary electro-catalytic activities towards ORR by a rotating-disk electrode method in alkaline electrolyte. The images obtained from a scanning electron microscope (SEM) and a transmission electron microscope (TEM) analyses confirm the formation of the star-shaped nanoparticles. Among the investigated nanostar catalysts, an AuNS5 with smaller size and a few branches showed the higher electrocatalytic activity towards ORR than other catalysts with a bigger size. In addition, the electron numbers transferred for all the catalysts are approximately two. The present study results infer that the size of the Au-based nanostars may influence greatly on their catalytic activity. The present study results show that the further improvement is needed for Au-based nanostar catalysts towards the ORR reaction.